PhiSiCal-Checkup: A Bayesian framework to validate amino acid conformations within experimental protein structures - Piyumi R. Amarasinghe; Lloyd Allison; Craig J. Morton; Peter J. Stuckey; Maria Garcia de la Banda; Arthur M. Lesk; Arun S. Konagurthu (Proceedings of the National Academy of Sciences, 2025)
As structural biology and drug discovery depend on high-quality protein structures, assessment tools are essential. We describe a new method for validating amino-acid conformations: “PhiSiCal ( ϕ ψ χ al) Checkup.” Twenty new joint probability distributions in the form of statistical mixture models explain the empirical distributions of dihedral angles ω , ϕ , ψ , χ 1 , χ 2 , … of canonical amino acids in experimental protein structures. Marginal and conditional probability distributions for subsets of dihedral angles are derived from these joint mixture models. Together, these distributions are employed to measure rapidly the information-theoretic “favorability” of any proposed experimental protein structure. The inferred statistical models and measures overcome several shortcomings and afford improvements over the current state of the art in amino-acid conformation verification. Experimental comparisons are made against current protein conformation verification software. In a number of examples, we pick up outliers that are invisible to current methods. We also calculate, as part of verification, the sensitivity of favorability to small changes in a proposed structure accounting for the precision of coordinates. In some cases a near neighbor of a proposed amino-acid conformation may be either less or more favorable. This raises the question, is the current reliance on fixed “thresholds” for validation a good thing? PhiSiCal-Checkup is freely available for online and offline (open-source) use from https://lcb.infotech.monash.edu.au/phisical/checkup .